Integrating Religion and Science: A Desecularistic-Implementative Curriculum Model in Indonesian Islamic Universities: Study of Holistic-Integrative Approach Curriculum Development in Islamic Higher Institutions in Indonesia - Andi Murniati (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
The Islamic Religious Education (PAI) curriculum at the university level in Indonesia is partial and dichotomous. Therefore, the construction of the PAI curriculum towards a desecularistic (unified) and implementable (applicable) approach is needed as a basis for providing education that is responsive to the demands of an increasingly progressive era. Educational curriculum based on a desecularistic-implementative approach is the basis for all activities, including coaching, educating, and developing the cognitive potential, character, and spirituality of students as a whole through an educational process without dichotomous barriers between religious knowledge and general knowledge (science). This research aims to analyze the construction of a PAI curriculum based on a desecularistic-implementative approach implemented at state Islamic universities (UIN) in Indonesia to solve the problematic educational dichotomy. This research uses a qualitative approach and the type of case study with participant observation and in-depth interviews as data collection techniques. Furthermore, the data was analyzed using the interactive model of Miles Huberman and Saldana. This research found that the construction of PAI curriculum was built through the "Spider Web" metaphor of UIN Yogyakarta, the "Ontological-Classificative Integration" of UIN Jakarta, the "Knowledge Tree" of UIN Malang, and the "Spiral Andromeda" of UIN Suska Riau. These four designs narrate the distinctive educational direction of each Islamic religious institution through its curriculum design but have similarities in terms of the "unification" of religious-Islamic values ​​with modern science. Implementation of the desecularistic-based curriculum downstream in the emergence of good graduates’ academic quality with a strong spiritual base and Islamic values. The strategy used by UIN includes three aspects: Preparing lectures with the "science integration" paradigm, implementing learning methods that internalize Islamic values, and adapting the Independent Campus Learning Program (MBKM).